Motivation, Leadership, Supply Chain Management toward Employee Green Behavior with Organizational Culture as a Mediator Variable - Rifdah Abadiyah; Anis Eliyana; Ahmad Rizki Sridadi (International Journal of Supply Chain Management, 2020)
This study aims to determine the effect of motivation, leadership and supply chain (information flow) management on employee green behavior through organizational culture as a mediator variable on the employees of PT. X in East Java. This research is a quantitative research type with a sample of 86 employees. By using Smart PLS as an analytical tool to examine the relationship between variables and mediation of organizational culture variable. The correlation of motivation and leadership to employee green behavior variables showed that motivation and leadership had a significant positive effect on employee green behavior, motivation had a significant positive effect on employee green behavior through organizational culture as a mediator variable, and organizational culture had a significant effect on green employee behavior at PT. X.